Scope of nano ophthalmology - Ali, Javed (International Journal of Pharmaceutical Investigation)
Topical eye drops are the most common dosage form for treating disorder related to the anterior segment of the eye. However, a large amount of drug delivered through the eye drops is lost through tear drainage and associated mechanisms that protect the eye against exposure to pernicious substances. An ideal drug delivery system for ocular drug delivery would be the one that increases the stay/contact time of the drug with the eye surface and would provide adequate concentration of drug at the site of action.